Linguistic Anomalies in Japanese: Forms, causes, and their grammatical, semantic, and cultural dimensions - Tatang Hariri; Takashi Hiraoka (BAHASTRA, 2026)
This study investigates anomalous sentences (ijoubun) in the Japanese language by examining their forms and underlying causes from grammatical, semantic, and sociocultural perspectives. Using a qualitative descriptive approach, data were collected from linguistic references and analyzed based on syntactic structure, semantic acceptability, and cultural appropriateness. The findings reveal three main categories of anomalies. First, grammatical anomalies, which arise from violations of structural rules, particularly incorrect particle usage (e.g., the misuse of o instead of to in kekkon suru) and inappropriate application of aspectual forms to stative verbs such as sobieru, aru, and iru. Second, honorific anomalies, caused by improper mixing of speech levels, especially between kenjougo and keigo, resulting in expressions that are structurally possible but pragmatically unacceptable. Third, sociocultural anomalies, where sentences are grammatically correct yet perceived as unnatural due to violations of Japanese cultural norms, including uchi–soto distinctions in greetings and contextual mismatches such as shitsugen in public discourse. These findings demonstrate that anomaly in Japanese cannot be explained solely by grammatical correctness but must also consider semantic harmony and cultural context. The study contributes to Japanese linguistics by providing a clearer classification of anomalous sentences and by establishing a conceptual distinction between grammaticality, naturalness, and acceptability. This integrated framework offers practical implications for language teaching, particularly in helping learners understand the limits of “natural” Japanese usage beyond formal grammar rules.